Ruminal metabolic development in conventionally or early weaned calves - Anderson, K.L.; Nagaraja, Tiruvoor G.; Morrill, J.L. (Kansas Agricultural Experiment Station, 2012)
Accelerating the weaning age of calves appeared to increase their ruminal metabolic activity. This was indicated by the lower ruminal pH and increased, total volatile fatty acid concentration of calves weaned at 4 wk of age compared with those weaned at 6 wk of age.
Keywords: Dairy; Ruminal microbes; Metabolic activity; Lactic acid; Volatile fatty acid